2019
DOI: 10.1038/s41419-019-1432-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-15b and miR-322 inhibit SETD3 expression to repress muscle cell differentiation

Abstract: SETD3 is a member of SET-domain containing methyltransferase family, which plays critical roles in various biological events. It has been shown that SETD3 could regulate the transcription of myogenic regulatory genes in C2C12 differentiation and promote myoblast determination. However, how SETD3 is regulated during myoblast differentiation is still unknown. Here, we report that two important microRNAs (miRNAs) could repress SETD3 and negatively contribute to myoblast differentiation. Using microRNA (miRNA) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…They play critical regulatory roles in posttranscription in gene expressions by targeting specific mRNAs for destabilizing the mRNA, repressing protein production, and translational silencing [6]. With this powerful regulatory function, miRNAs contribute to various biological processes including proliferation [7], differentiation [8], and apoptosis [7]. Abundant evidences have showed that miRNAs are involved in pathogenesis of many diseases, especially tumor development [9].…”
Section: Introductionmentioning
confidence: 99%
“…They play critical regulatory roles in posttranscription in gene expressions by targeting specific mRNAs for destabilizing the mRNA, repressing protein production, and translational silencing [6]. With this powerful regulatory function, miRNAs contribute to various biological processes including proliferation [7], differentiation [8], and apoptosis [7]. Abundant evidences have showed that miRNAs are involved in pathogenesis of many diseases, especially tumor development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle-specific miRNAs included miR-1, miR-133a/b, and miR-206, which were involved in myoblast proliferation and differentiation by regulating the expression of target genes, such as histone deacetylase 4, serum response factor, the myogenic differentiation family, and other myogenic transcriptional factors [9][10][11]. Other non-specific muscle miRNAs have also been involved in the regulation of muscle growth and development, such as miR-17, miR-19, miR-15b, miR-322, miR-208b, miR-26a, miR-30, miR-128a, miR-203a, miR-214, and miR-3906 [12][13][14][15]. For example, miR-26a promoted myoblast differentiation by regulating the expression of target genes Smad1 and Smad4 [16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-322/-503 was required in myoblast differentiation miR-322/-503 was revealed to promote cardiac differentiation by targeting Celf1 in early cardiac progenitor cells 39 , but its function in myoblast differentiation was still under debate 40,41 . We performed β-galactosidase staining on miR-322/-503 lacZ knock-in mouse E10.5 embryos.…”
Section: Resultsmentioning
confidence: 99%
“…The expressions of both miRNAs are under the control of the same cis -elements. miR-322/-503 was reported to function mainly in cancer 31 33 , angiogenesis 34 , 35 , cardiovascular diseases 36 38 , and development fields 39 41 . Our previous study demonstrated that miR-322/-503 was enriched in early cardiac progenitors and promoted cardiac differentiation by repressing Celf1 39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation